Pelatihan Manajemen Madrasah Diniyah Takmiliyah Awwaliyah (MDTA) Untuk Kemampuan Manajemen lembaga Di Desa Kedung Bendo Kecamatan Sooko Kabupaten Mojokerto: Peningkatan Kompetensi Manajerial Lembaga Pendidikan Nonformal Islam Melalui Pelatihan Partisipatif - Moh Muntholib; Nelud Darajaatul Aliyah (Sekolah Tinggi Agama Islam Al-Muntahy, 2025)
This study focuses on enhancing managerial competence and institutional effectiveness at Madrasah Diniyah Takmiliyah Awwaliyah (MDTA) Kedung Bendo through the implementation of participatory management training based on the Participatory Action Research (PAR) approach. The primary objective is to develop a training model that integrates Islamic ethical values, institutional professionalism, and the principle of collective participation in managing non-formal Islamic educational institutions. This research employed the PAR approach consisting of four reflective stages: diagnosis, planning, action, and reflection. Data were collected through participatory observation, in-depth interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that participatory training significantly improved the managerial capacity of teachers and administrators in strategic planning, organizational role division, internal coordination, and documentation systems. Moreover, the program fostered a collaborative work culture and a renewed spiritual awareness that strengthened moral responsibility and institutional sustainability. Conceptually, this study expands the theoretical discourse of Islamic educational management by linking modern management theory, participatory leadership, and the maqāṣid al-sharī‘ah framework. The practical implication highlights the importance of participatory-based training as a strategic approach to strengthening the professionalism, accountability, and global competitiveness of non-formal Islamic educational institutions.